Structural Design of Electric Steering Gear Transmission Device of Aircraft - Wang Li Sheng Zhixiao Cao Lei (Jixie chuandong)
The cylindrical gears are used to drive the traditional electric steering gear. There are many problems such as heavy weight，complex space structure and more transmission series，so the transmission efficiency is low. In view of the above problems，harmonic gear transmission is used instead of cylindrical gear transmission to determine the overall scheme，component structure. The Creo software is used to build the three-dimensional solid model of the transmission device，and the trial-manufacture of the principle prototype is completed after processing，manufacturing， installation and commissioning. The study results show that the scheme of applying harmonic gear transmission on electric steering gear transmission device is feasible，a foundation for theoretical and experimental research of optimizing electric steering gear transmission is laid.